2004
DOI: 10.1080/10473289.2004.10470941
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Destruction of Dichloromethane Using Perovskite-Type Oxide Catalysts

Abstract: Dichloromethane (DCM, also known as methylene chloride [CH 2 Cl 2 ]) is often present in industrial waste gas and is a valuable chemical product in the chemical industry.This study addresses the oxidation of airstreams that contain CH 2 Cl 2 by catalytic oxidation in a tubular fixed-bed reactor over perovskite-type oxide catalysts. This work also considers how the concentration of influent CH 2 Cl 2 (C 0 ϭ 500 -1000 ppm), the space velocity (GHSV ϭ 5000 -48,000 1/hr), the relative humidity (RH ϭ 10 -70%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These byproducts are formed in much lower proportion over LaMnO 3 . Manganites appear to be more selective to CO 2 and more stable than cobaltites …”
Section: Oxidation Reactionsmentioning
confidence: 97%
See 1 more Smart Citation
“…These byproducts are formed in much lower proportion over LaMnO 3 . Manganites appear to be more selective to CO 2 and more stable than cobaltites …”
Section: Oxidation Reactionsmentioning
confidence: 97%
“…Manganites appear to be more selective to CO 2 and more stable than cobaltites. 454 Destruction of C2-CHC was also investigated by Sinquin et al over LaMnO 3 . 455 As for C1-CHC, water plays a significant role and H 2 O/O 2 mixtures are recommended for destruction of these compounds.…”
Section: Volatile Organic Compounds (Voc) Eliminationmentioning
confidence: 97%
“…9 They have found that the metallic components of catalysts, such as zinc (Zn), titanium (Ti), copper (Cu), iron (Fe), chromium (Cr), vanadium (V), Cerium (Ce), manganese (Mn), nickel (Ni), and cobalt (Co), can all be used in a spinel structure. Therefore, theoretically, the metallic oxide manufactured from FP should exhibit some catalytic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…These are also recognized as chlorinated volatile organic compounds (CVOCs), which are very harmful to the environment and human body, thus its exposure should be suppressed. The oxidative decomposition of CVOCs by reacting them with dioxygen can convert CVOCs to harmless substances such as carbon dioxide, in which a number of efficient catalysts have been studied for the catalytic oxidation of CVOCs, including zeolites, [8][9][10] perovskites, [11][12][13][14] noble metals [15][16][17][18][19] and metal oxides. [20][21][22][23][24][25][26][27][28][29] The complete oxidation of CVOCs to CO 2 would be efficient approach to solve the environmental problems of CVOCs, but another potential way to convert the CVOCs into value-added intermediates could be considered.…”
Section: Introductionmentioning
confidence: 99%